THE EFFECT of The PROBLEM BASED LEARNING (PBL) MODEL on STUDENTS’ SCIENCE LITERACY SKILLS on INDONESIA’S ECOLOGY and BIODIVERSITY MATERIALS - Fatmawati, Junita; Lestari, Tuti; Putri, Azza Nuzullah; Azhar, Aulia (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Science literacy is the capacity to use clinical information to pick out troubles and draw conclusions based totally on proof so that you can understand and make selections approximately nature and modifications made to nature via human activities. Based on PISA data and preliminary study data, the literacy of science competencies of Indonesian students is still low. One of the learnings that has a positive influence on science literacy is problem-based learning (PBL). Methods: This study applied the Quasi Experiment method with the Nonequivalent Control Group Design. This research was conducted at SMPN 1 Gunung Talang, Solok Regency, West Sumatra in class VII in the 2023/2024 school year. Results: The average value of the experimental class is higher than the average of the control class on the posttest data. The hypothesis test results show that t'count 3.372 is greater than t'table 2.008, so H0 is rejected and H1 is accepted. Conclusion: The application of the Problem Based Learning (PBL) model affects the science literacy skills of students in Indonesian Ecology and Biodiversity material.